Towards a continuous non-invasive assessment of intra-abdominal pressure based on bioimpedance and microwave reflectometry: A pilot run on a porcine model. (July 2018) - David, Marcelo; Raviv, Aviad; Peretz, Aviad; Berkovich, Uriel; Pracca, Francisco
Abstract: In this work we describe two novel indirect intra-abdominal pressure (IAP) assessment techniques, based on electrical bioimpedance and microwave reflectometry measurements. A pilot run was performed on a female Sus scrofa domesticus (domestic pig). IAP was induced by inflation of the abdominal cavity using a trocar placed near the umbilicus over the linea alba at a depth of 1 cm. The abdominal cavity was inflated to different IAP values. The whole run was done within one hour since the subject was sacrificed. An exponential trend linking between the bioimpedance values at 99.8 kHz and the IAP was found, with drastically reduced sensitivity for IAP above 7 mmHg. Also, a linear relationship between IAP and the microwave reflectometry measurements at 4.25 GHz was established. Although further research is needed to optimize the sensitivity of the bioimpedance system, we draw the conclusion that the use of electromagnetic spectrometry methods might be developed into novel techniques for performing a continuous non-invasive assessment of changes in IAP.